Genetic characterization of Golden mahseer (Tor putitora) populations using mitochondrial DNA markers. (10th September 2013) - Sati, Jyoti; Kumar, Rohit; Sahoo, Prabhati Kumari; Patiyal, Rabindar S.; Ali, Shahnawaz; Barat, Ashoktaru
Abstract: Golden Mahseer ( Tor putitora ) is an economically important fish of India and Southeast Asia. The present study examined the genetic variations between seven geographically isolated populations of T. putitora using Cyt b (Cytochrome b) and ATPase6/8 gene sequences of mitochondrial DNA. Analysis of 133 sequences of Cyt b (1141 bp) and 130 sequences of ATPase6/8 gene (842 bp) revealed 47 and 44 haplotypes, respectively. The estimated haplotype and nucleotide diversity was high in River Jia Bhoreli (Bhalukpong) population ( h  = 1.00000, π  = 0.007121 for Cyt b and h  = 0.90441 π  = 0.004867 for ATPase6/8 ). Results of AMOVA indicated that majority of the genetic variations in both genes were due to variation among populations (60.79% for Cyt b and 51.41% for ATPase6/8 gene). The pairwise F ST comparison and neighbor-joining tree revealed high genetic divergence of River Jia Bhoreli population from other populations. The understanding of genetic variations of T. putitora populations will play a key role in conservation and management of this endangered fish species.